THE GABBROIC COMPLEX OF THE WESTERN OPHIOLITIC BELT, NORTHERN ALBANIA: AN EXAMPLE OF MULTILAYERED SEQUENCE IN AN INTERMEDIATE-SPREADING OCEANIC RIDGE - Cortesogno, Luciano; Gaggero, Laura; Jaho, Etleva; Marroni, Michele; Pandolfi, Luca; Shtjefanaku, Dode (Ofioliti, 1998)
The paired ophiolitic belts of Albania are characterized by two contrasting stratigraphic and compositional signatures. Whereas the Eastern belt shows a thick sequence with IAT affinity, the Western ophiolites are characterized by a MOR-type sequence with a thickness not exceeding 4 km. The western Mirdita ophiolite includes a mantle section overlain by a gabbroic complex consisting of cumulus dunites, melatroctolites, troctolites, norites, gabbros, diorites, Fe-Ti ox-gabbro-diorites with minor plagiogranites. The gabbroic complex, that everywhere shows a reduced thickness, is overlain by a sheeted dike complex with MORB affinity. The cumulus pile, from layered melatroctolites to diorites, is characterized by magmatic flow-related structures, such as foliation and lineation. The magmatic foliation is cut at low angle by mylonitic shear zones with high-T amphibolite facies assemblages. The shear zones are generally recognized in the lower-middle part of the gabbroic complex, whereas to the top of the sequence the brittle deformation prevails. The mylonitic shear zones are cut in turn by basaltic dikes and plagiogranitic bodies. The intrusion of basaltic dikes with IAT affinity represents a later magmatic event, that suggest a change in geotectonic environment. On the whole, igneous and metamorphic features, as well as the thickness and composition of the basaltic cover on gabbros, support that the western belt of Albanian ophiolites representative of a ridge with intermediate spreading rate.